Children's Social Emotional Relationship to Digital Parenting - Rahimah Rahimah (International Journal Reglement & Society (IJRS), 2021)
Digital parenting or digital parenting is to provide clear boundaries for managing and supervising children against the use of digital devices. Currently, many families in Indonesia have not implemented digital parenting, causing children to be lazy to socialize, the intensity of family communication is reduced. In addition, children are difficult to communicate with, are not sensitive to the environment, children become passive, do not listen to their parents, cannot contain their emotions, and are very slow in responding when ordered to do something. In this case, people give gadgets to their children for the purpose of making it easier for parents to take care of their children. The results of the research related to the above discussion are applying the rules and agreements related to the use of gadgets; guide and assist children; using parental control, and balancing the digital world of children with the real world. The role of digital parenting on prosocial behavior includes; as prosocial behavior education; instilling prosocial values from children's shows; and as a child's control of inappropriate viewing; and balance the world of play with gadgets and the real world. The role of digital parenting on children's logical thinking as education as well as entertainment for children; stimulate logical thinking; controlling, supervising, guiding children and as an effort to prevent children from being addicted to gadgets.